Production Process and Consumer Perception of Luwak Coffee (Case at PTPN XII Kalisat, Bondowoso and Care Rollaas Surabaya, East Java) - Tommy Wicaksono (Central Research Institute For Agriculture, 2022)
Coffee is a commodity that can be made for drinks. Many people who consume coffee, feel the pleasure and aroma of coffee. Coffee is now a necessity that is needed by the community. The need for coffee is increasing, because almost all people who smoke cigarettes smoke their cigarettes by consuming a cup of coffee. One of Indonesia's mainstay agricultural commodities, which until now is very well known domestically and internationally, is Luwak coffee. Kopi Luwak is a type of coffee made from coffee beans that have been eaten and passed through the digestive tract of a type of civet animal called the Luwak. This research is an analysis of qualitative descriptive data where the data collected in this study are Primary Data and Secondary Data and for data collection methods, namely interviews, observation and documentation. The aims of this research are to (1) identify the characteristics of civet coffee consumers (2) Knowing the production process of Kopi Luwak. (3) Knowing consumer perceptions of Kopi Luwak. This type of research is descriptive research. Descriptive research is intended for careful measurement of the phenomena that occur.